ARCHEOLOGY OF LATE MEDIEVAL HALYCH AS A «CHURCH CITY» AND RELIGIOUS CENTER OF HALYCHYNA (MIDDLE OF THE 13th CENTURY – 1785) - TOMENCHUK, Bohdan; MELNYCHUK, Oleh (Halych. Scientific work collection, 2017)
The article shows the main results of archaeological research of ancient Halych in the late medieval period of its history as a «church city», a religious and spiritual center of Halychyna (middle of the ХІІІ century – 1785). Development of the of historical topography of Halych/Krylos is characterized in detail in three stages: middle of the XIII century – 1596; 1596–1700; 1700/1785. The complex historical archaeological analysis of each of them allows to see clearly the ways and prospects of further scientific studies.